The effect of different seeding concentration on diamond nucleation density of WC-6% Co [electronic resources] - Lai, Hui Yan, 1988- author; Engku Mohammad Nazim Engku Abu Bakar, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2012